2019
DOI: 10.1002/cpt.1515
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using Pazopanib With Food vs. Fasted on Pharmacokinetics, Patient Safety, and Preference (DIET Study)

Abstract: Pazopanib is taken fasted in a fixed oral daily dose of 800 mg. We hypothesized that ingesting pazopanib with food may improve patients’ comfort and reduce gastrointestinal (GI) adverse events. Therefore, we investigated the bioequivalent dose of pazopanib when taken with food compared with 800 mg pazopanib taken fasted. In addition, we investigated the differences in GI toxicity, patient satisfaction, and patient's preference for either intake. The intake of 600 mg pazopanib with food resulted in a bioequival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 18 publications
0
46
1
Order By: Relevance
“…Heath et al demonstrated a higher exposure to pazopanib when administering pazopanib concomitant with food . Thereafter, it was demonstrated that a lower dose of pazopanib can be administered with food while maintaining bio‐equivalent C trough levels of a higher dose without food (n = 78) while gastrointestinal toxicity was comparable when a reduced dose of pazopanib was taken with food . Recently, another study reported that administering pazopanib with food did not increase the risk of toxicity (n = 16), while all but two patients reached adequate C trough.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Heath et al demonstrated a higher exposure to pazopanib when administering pazopanib concomitant with food . Thereafter, it was demonstrated that a lower dose of pazopanib can be administered with food while maintaining bio‐equivalent C trough levels of a higher dose without food (n = 78) while gastrointestinal toxicity was comparable when a reduced dose of pazopanib was taken with food . Recently, another study reported that administering pazopanib with food did not increase the risk of toxicity (n = 16), while all but two patients reached adequate C trough.…”
Section: Methodsmentioning
confidence: 99%
“… Not having to fast around the pazopanib intake may positively affect quality of life for cancer patients, especially those experiencing difficulty in maintaining bodyweight. The preference of patients for intake with food was shown in the DIET study where 68% of patients preferred the intake of pazopanib with food compared to without food …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 Furthermore, oral absorption of pazopanib is shown to increase when given with food. 5,6 Patients starting with the recommended dosage (800 mg/d without food) often experience discontinuation because of intolerable toxicities. 7 Therefore, it is necessary to develop an individualized dosing strategy for pazopanib therapy.…”
Section: Introductionmentioning
confidence: 99%